The Influence of Servant Leadership and Compensation on Organizational Citizenship Behaviour (OCB) with Job Satisfaction as a Mediation Variable - Fathkhurrahman, Helmi Ikhsan; Mohyi, Achmad; Mu'ammal, Immanuel (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research was conducted to determine and analyze the influence of servant leadership and compensation on organizational citizenship behavior, with job satisfaction as a mediating variable. This type of research uses explanatory research with a quantitative approach. The data collection technique in this research uses a questionnaire. This study's population consisted of contractor PT Ometraco Arya Samanta employees, totaling 75 employees. The data analysis method used is path analysis assisted by SmartPLS 4.0 software. The research results found that servant leadership influences job satisfaction. Compensation influences job satisfaction. Servant leadership influences organizational citizenship behavior. Compensation does not affect organizational citizenship behavior. Job satisfaction influences organizational citizenship behavior. Servant leadership affects organizational citizenship behavior with job satisfaction as a mediating variable, and compensation does not affect organizational citizenship behavior with job satisfaction as a mediating variable.